PENGARUH ANGGARAN BERBASIS KINERJA DAN KESULITAN MENENTUKAN UKURAN KINERJA TERHADAP AKUNTABILITAS KINERJA PEMERINTAH DAERAH - Shella Gilby Sapulette; Theresia Febiengry Sitanala (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to empirically examine the effect of performance-based budgeting and the difficulty of determining performance measures on performance accountability using a quantitative approach and tested with SPSS 24. This research was conducted on OPD of Ambon City government with a research sample of 69 employees. The sampling technique uses purposive sampling. The test results show that performance-based budgeting has a positive and significant effect on local government performance accountability, while difficulty determining performance measures does not affect local government performance accountability